Circulating Plasmacytoid and Conventional Dendritic Cells Are Numerically and Functionally Deficient in Patients With Scrub Typhus - Kang, Seung-Ji; Park, Ki-Jeong; Jin, Hye-Mi; Cho, Young-Nan; Oh, Tae Hoon; Kim, Seong Eun; Kim, Uh Jin; Park, Kyung-Hwa; Jung, Sook-In; Kim, Tae-Ok; Kim, Hyo Shin; Jo, Young-Goun; et al. (Frontiers in Immunology, 2021)
Background Dendritic cells (DCs) are specialized antigen-presenting cells known to bridge innate and adaptive immune reactions. However, the relationship between circulating DCs and Orientia tsutsugamushi infection is unclear. Therefore, this study aimed to examine the level and function of plasmacytoid DCs (pDCs) and conventional DCs (cDCs), two subsets of circulating DCs, in scrub typhus patients. Methods The study included 35 scrub typhus patients and 35 healthy controls (HCs). pDC and cDC levels, CD86 and CD274 expression, and cytokine levels were measured using flow cytometry. Results Circulating pDC and cDC levels were found to be significantly reduced in scrub typhus patients, which were correlated with disease severity. The patients displayed increased percentages of CD86+ pDCs, CD274+ pDCs, and CD274+ cDCs in the peripheral blood. The alterations in the levels and surface phenotypes of pDCs and cDCs were recovered in the remission state. In addition, the production of interferon (IFN)-α and tumor necrosis factor (TNF)-α by circulating pDCs, and interleukin (IL)-12 and TNF-α by circulating cDCs was reduced in scrub typhus patients. Interestingly, our in vitro experiments showed that the percentages of CD86+ pDCs, CD274+ pDCs, and CD274+ cDCs were increased in cultures treated with cytokines including IFN-γ, IL-12, and TNF-α. Conclusions This study demonstrates that circulating pDCs and cDCs are numerically deficient and functionally impaired in scrub typhus patients. In addition, alterations in the expression levels of surface phenotypes of pDCs and cDCs could be affected by pro-inflammatory cytokines.